PENGAMBILAN KEPUTUSAN PEMILIHAN HANDPHONE TERBAIK DENGAN ANALYTICAL HIERARCHY PROCESS (AHP) - Antono Adhi (Jurnal Ilmiah Dinamika Teknik, 2010)
The Analytic Hierarchy Process (AHP) is a structured technique for dealing with complex decisions. Rather than prescribing a "correct" decision, the AHP helps decision makers find one that best suits their goal and their understanding of the problem. It is a process of organizing decisions that people are already dealing with, but trying to do in their heads. When AHP is used to help decision of which handphone is choosed (Blackberry, Nokia, Sony Erickson), it need some criterias. The criterias are price, technology and design while price is derived to price of product, sparepart, and reselling. Technology is derived to camera, feature, and battery. Design is derived to qwerty, touchscreen and common touch. The result give weights for every alternative. Blackberry weight is 0.67, Nokia weight is 0.21, and Sony Erickson weight is 0.12. That’s mean that Blackberry is better than the others, followed by Nokia and then Sony Erickson.   Keyword : AHP, Decision, Criteria, Alternative